2017
DOI: 10.1186/s40854-017-0070-0
|View full text |Cite
|
Sign up to set email alerts
|

Financial innovation and economic growth in Bangladesh

Abstract: Background: This study provides evidence for the financial innovation in the financial system that resulted in the economic growth of Bangladesh from 1980-2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 65 publications
12
52
0
Order By: Relevance
“…We also observed that the elasticities of financial innovation toward economic growth were positively influenced in both the short-run and long-run periods. These findings align with Mwinzi (2014), Qamruzzaman and Jianguo (2017), and Beck et al (2014). Chou and Chin (2011) suggested that financial innovation increases the volume of financial product variety along with efficient financial services, eventually promoting financial-development-led economic growth.…”
Section: Conclusion and Recommendationssupporting
confidence: 80%
See 1 more Smart Citation
“…We also observed that the elasticities of financial innovation toward economic growth were positively influenced in both the short-run and long-run periods. These findings align with Mwinzi (2014), Qamruzzaman and Jianguo (2017), and Beck et al (2014). Chou and Chin (2011) suggested that financial innovation increases the volume of financial product variety along with efficient financial services, eventually promoting financial-development-led economic growth.…”
Section: Conclusion and Recommendationssupporting
confidence: 80%
“…Research in the past decade has used bank credit to the private sector as a proxy indicator for financial innovation (e.g., Adu-Asare Idun and Aboagye 2014; Michalopoulos et al 2009). However, many empirical studies have used the ratio of broad-to-narrow money as a proxy for financial innovation (e.g., Bara and Mudxingiri 2016;Qamruzzaman and Jianguo 2017;Ansong et al 2011;Mannah-Blankson and Belnye 2004). This study followed the same path for investigation.…”
Section: Datamentioning
confidence: 99%
“…These study findings are supported by empirical studies conducted by Boubakari and Jin (2010); Coşkun et al (2017); and Pradhan et al (2014aPradhan et al ( , 2015. Furthermore, the finding of the long-run association between financial innovation and economic growth is also in line with Ajide (2015); Qamruzzaman and Wei (2017); and Bara and Mudzingiri (2016). Table 5.…”
Section: Ardl Bounds Testing For Cointegrationsupporting
confidence: 78%
“…To capture the financial innovation impact on economic growth, a larger number of studies repeatedly used broad to narrow money (M2/M1), where M1, known as narrow money, normally includes coins and notes in circulation and other money equivalents that are easily convertible into cash. M2 includes M1 plus short-term time deposits in banks and 24-h money market funds (see for example, Ansong et al 2011; Mannah-Blankson and Belnye 2004; ; Bara and Mudzingiri 2016;Arrau 1991;Qamruzzaman and Wei 2017).…”
Section: Variable Definition and Sourcesmentioning
confidence: 99%
“…In addition to the results, in all other sectors except MC and CH sectors, causality relation was observed at different rates from credit interest rates to industrial production index. There are also some studies in the literature in which the causality relation from bank credits to industrial production index is partially or completely observed (Toby and Peterside, 2014;Chisasa, 2014;Rahman et al, 2015;Stolbov, 2017;Qamruzzaman and Jianguo, 2017) However, there are also studies in which the causality relationship from bank loans to industrial production index cannot be found (Dal Colle, 2011;Marques et al, 2013;Tripathi and Kumar, 2015;Adeola and Ikpesu, 2016). The casual relationship between the industrial production index and the bank credit volume and credit interest rates give clues that production is financed by bank loans.…”
Section: Resultsmentioning
confidence: 99%